Clinico-pathological and treatment characteristics of HIV and non-HIV related vulvar cancers: Analysis of a South African cohort. - Adekunle Emmanuel Sajo; Edwin Francis Mnisi; Sheynaz Bassa; Cathy Visser; Greta Dreyer (PLoS ONE)
Objective The main objective of this study was to describe the clinical, pathological and treatment characteristics of patients with vulvar cancer who had surgery and or radiotherapy at Steve Biko Academic Hospital. The absolute and relative disease burden, trends over the time period were also analyzed. Materials and methods This was a retrospective study that described women with vulvar cancer who presented to the Gynaecology Oncology and Radiation Oncology departments of the hospital between January 2012 and December 2022. Their clinical, pathology and radiotherapy treatment records were reviewed for this study. Results 317 vulvar cancer cases between 2012 and 2022 were included in the analysis. The average age was 45.1±12.7. Forty percent of the participants were younger than 40 years. More than 75% of them were women living with HIV and were all on antiretroviral treatment. The average age of those who were HIV positive was 20 years lower than their HIV negative counterparts, p <0.0001. Their mean haemoglobin (Hb) at presentation was 10.7g/dL. Squamous cell carcinoma was the most common histological type in 96.5% of cases. Sixty four percent of the cases presented in advanced stage. About 48% of those who had primary radiation received curative doses. The median time to completion of radiotherapy treatment was higher among those who received primary radiotherapy as compared to those who received adjuvant treatment, 51.5 vs 46 days, p 0.039. The annual average age decreased from 56 years to as low as 40 years, a mean difference of 16 years, p 0.012. Conclusion It is striking that vulvar cancer is no longer a disease of elderly women. Its incidence is now high among women below 50 years. The study also showed an upward trend in the number of vulvar cancer cases in contrast to the declining average age at diagnosis. There is need for more vulvo-perineal surveillance of HIV positive women to detect early stage of vulvar cancers.